Taxonomic purgatory: Sorting out the wasp genus Myzinum Latreille in North America (Hymenoptera, Tiphiidae, Myzininae) - Kimsey, Lynn S. (Zootaxa, 2009)
The ten North American species of the tiphiid genus Myzinum Latreille are reviewed, redescribed and a key to species provided. The new species cocoritensis is described from southern Arizona, USA and northern Sonora, Mexico. Three genera described by Argaman 1994 (Tokoparta, Fikoplesa and Ekepirka) are synonymized under Myzinum Latreille. Myzinum spilonotum (Cameron 1908) is newly synonymized under maculatum (Fabricius 1793), Myzinum beryli (Brimley 1927) under obscurum (Fabricius 1805), and the two subspecies of Myzinum beryli, parksi Krombein 1938 and patei Krombein 1938, are synonymized under carolinianum (Panzer 1806). Myzinum fulviceps (Cameron 1900) is removed from synonymy under quinquecinctus (Fabricius 1775) and is treated as a valid species.